Den vedblivende utopi - Abensour, Miguel (K&K - Kultur og Klasse, 2012)
PERSISTENT UTOPIA | Persistent utopia is not to be confused with the conservative notion of an eternal utopia as a static and authoritarian ideal. Rather, persistent utopia is an impulse towards freedom and justice. It is a fragile phenomenon which is seeking to avoid the closure of reality through a constant displacement. The sites of the persistent utopia can be located at two different levels: through the ontological thinking of Ernst Bloch and through the ethical philosophy of Emmanuel Levinas which takes the encounter as its point of departure. The present forms of the persistence of utopia can be seen, e.g., in the “new utopian spirit” as a response to the dialectics of emancipation, and in the relation between utopia and democracy.